THE EFFICACY OF TIKTOK SHORT VIDEO TO ELEVATE THE STUDENTS’ ACHIEVEMENT ON THE VOCABULARY LEARNING: THE EXPERIMENTAL STUDY IN SMP NEGERI 3 SUTOJAYAN - Silvi Wahyu Herida Saputri; Hesty Puspita Sari; Yusniarsi Primasari; Supriyono Supriyono (Program Studi PGSD Universitas Flores, 2025)
This study aims to investigate the efficacy of TikTok short videos as a tool to improve students' achievement in vocabulary learning at SMP Negeri 3 Sutojayan Blitar. The research employs a pre-experimental design with a one-group pre-test and post-test methodology. A total of 30 seventh-grade students from Class 7A were involved during the period of April to May 2024. Data were collected through a pre-test, a treatment session involving TikTok videos, and a post-test to measure the improvement in students' vocabulary. The analysis was conducted using quantitative methods based on Sugiyono's (2019) framework. The results of the study indicate that the use of TikTok short videos significantly improved students' performance in vocabulary learning. The study concludes that integrating social media platforms such as TikTok can be an effective strategy in vocabulary learning, offering an engaging blend of entertainment and education. The study recommends further research to explore the use of other digital tools in education.